Decadal predictability of North Atlantic sea surface temperature and climate - Sutton, RT; Allen, M (1997)
The weather at middle latitudes is largely unpredictable more than a week or so in advance, whereas fluctuations in the ocean may be predictable over much longer timescales. If decadal fluctuations in North Atlantic sea surface temperature could be predicted, it might be possible to exploit their influence on the atmosphere to forecast decadal fluctuations in climate. Here we report analyses of shipboard observations that indicate significant decadal predictability of North Atlantic sea surface temperature, arising from the advective propagation of sea-surface-temperature anomalies and the existence of a regular period of 12-14 years in the propagating signals. The same timescale can be identified in a dipole-like pattern of North Atlantic sea-level pressure variability. We propose a mechanism which may connect these oceanic and atmospheric fluctuations, possibly as part of a coupled ocean-atmosphere mode of variability. Our results are encouraging for the prospects of forecasting natural fluctuations in the climate of the North Atlantic region several years in advance.